International differences in lung cancer survival by sex, histological type and stage at diagnosis: an ICBP SURVMARK-2 Study. Issue 4 (19th July 2021) - Araghi, Marzieh; Fidler-Benaoudia, Miranda; Arnold, Melina; Rutherford, Mark; Bardot, Aude; Ferlay, Jacques; Bucher, Oliver; De, Prithwish; Engholm, Gerda; Gavin, Anna; Kozie, Serena; Little, Alana; et al.
Abstract : Introduction: Lung cancer has a poor prognosis that varies internationally when assessed by the two major histological subgroups (non-small cell (NSCLC) and small cell (SCLC)). Method: 236 114 NSCLC and 43 167 SCLC cases diagnosed during 2010–2014 in Australia, Canada, Denmark, Ireland, New Zealand, Norway and the UK were included in the analyses. One-year and 3-year age-standardised net survival (NS) was estimated by sex, histological type, stage and country. Results: One-year and 3-year NS was consistently higher for Canada and Norway, and lower for the UK, New Zealand and Ireland, irrespective of stage at diagnosis. Three-year NS for NSCLC ranged from 19.7% for the UK to 27.1% for Canada for men and was consistently higher for women (25.3% in the UK; 35.0% in Canada) partly because men were diagnosed at more advanced stages. International differences in survival for NSCLC were largest for regional stage and smallest at the advanced stage. For SCLC, 3-year NS also showed a clear female advantage with the highest being for Canada (13.8% for women; 9.1% for men) and Norway (12.8% for women; 9.7% for men). Conclusion: Distribution of stage at diagnosis among lung cancer cases differed by sex, histological subtype and country, which may partly explain observed survival differences. Yet, survival differences were also observed within stages, suggesting that quality of treatment, healthcare system factors and prevalence of comorbid conditions may also influence survival. Other possible explanations include differences in data collection practice, as well as differences in histological verification, staging and coding across jurisdictions.